Tumor Necrosis Factor-Alpha Antagonist Interferes With the Formation of Granulomatous Multinucleated Giant Cells: New Insights Into Mycobacterium tuberculosis Infection - Mezouar, Soraya; Diarra, Issa; Roudier, Jean; Desnues, Benoit; Mege, Jean-Louis (Frontiers in Immunology, 2019)
More than half of tuberculosis cases in the world are due to resuscitation of dormant Mycobacterium tuberculosis (Mtb) sequestered into cell-derived structures called granulomas. It is fairly admitted that cytokines and more particularly Tumor Necrosis Factor (TNF)- is critical in the control of Mtb infections and that anti-TNF- drugs constitute one of the main risk factors for reactivation of latent Mtb infection. The aim of this study was to evaluate the role of etanercept, a dimeric fusion protein consisting of the extracellular ligand-binding portion of the human p75 TNF receptor linked to the Fc portion of human IgG1, in an in vitro model of human tuberculous granuloma. We showed that etanercept slightly delayed the formation of granuloma and reduced the generation of multinuclear giant cells (MGCs). In addition, etanercept exacerbated the expression of M1 polarization genes but also induced interleukin (IL)-10 release. In addition, our results indicated that etanercept inhibited cell fusion in an IL-10-dependent manner. Moreover, adalimumab, a human monoclonal anti-TNF- IgG1 inhibited MGC formation in granuloma, without altering IL-10 secretion and induced macrophage apoptosis. Taken together, our data provides new insights into the role of TNF- blockers in MGCs formation and the impact of such immunomodulatory drugs on tuberculous granuloma maturation.